Damage classification in reinforced concrete beam by acoustic emission signal analysis - Shahidan, Shahiron; Pulin, Rhys; Muhamad Bunnori, Norazura; M. Holford, Karen (Elsevier, 2013)
Acoustic Emission (AE) is a non-destructive testing technique which can be used to identify both the damage level and the nature of that damage such as tensile cracks and shear movements at critical zones within a structure. In this work, the acoustic emission parameters of amplitude, rise time, average frequency and signal strength were used to classify the damage and to determine the damage level. Laboratory experiments were performed on a beam (150 x 250 x 1900 mm). The acoustic emission analysis was successfully used to determine crack movements and classify damage levels in accordance with the observations made during an increasing loading cycle.